PENGARUH PELATIHAN DAN MOTIVASI TERHADAP KINERJA KARYAWAN BADAN PENANGGULANGAN BENCANA DAERAH DI GRESIK: Training, Motivation and Performance - Kusumaningrum, Dini (GEMA EKONOMI, 2020)
This study aims to determine the effect of training on employee performance at the Regional Disaster Management Agency in Gresik, the influence of motivation on the performance of the employees of the Regional Disaster Management Agency in Gresik, and the effect of training and motivation on employee performance at the Regional Disaster Management Agency in Gresik. This type of research is a survey. The population and sample in this study are employees who are still working at the Regional Disaster Management Agency in Gresik. The sampling method was total sampling with 38 respondents. Data were collected using a questionnaire that has been tested for its validity and reliability. This study uses a quantitative research approach to multiple regression analysis. The result of this research is that training and motivation variables simultaneously affect the employee performance of the Regional Disaster Management Agency in Gresik. This is evidenced by the value of Fcount (448,000) is greater than Ftable (3.24) and the significant level of F 0.000 is smaller than alpha = 0.05.